2007
DOI: 10.1007/s12011-007-8012-8
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction Between Selenium Status, Sex Hormones, and Thyroid Metabolism in Adolescent Girls in the Luteal Phase of their Menstrual Cycle

Abstract: The objective of the present work was to study all physiological relationships among selenium status (SeS), sex hormones secretion (SH), and thyroid metabolism (ThM) in healthy adolescent girls, at one time. Forty-four girls aged 13.4-16.6 years (mean age, 14.5 +/- 0.5 years) entered the statistical model. Parameters reflecting SeS: plasma selenium concentration (Se) and plasma glutathione peroxidase activity (GPX3); SH: serum estradiol (E2) and progesterone (P4); age of menarche (AoM); and ThM: thyroid stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
1
11
1
Order By: Relevance
“…According to recent studies, Krakow region is characterized by mild selenium deficiency [36,37] and iodine near repletion on the population level [38]. However, mild to moderate iodine deficiency still exists in a large fraction of pregnant women [21], and our results applying to pregnant women from this region may deviate from results obtained for female populations with other iodine and selenium status.…”
Section: Discussioncontrasting
confidence: 57%
“…According to recent studies, Krakow region is characterized by mild selenium deficiency [36,37] and iodine near repletion on the population level [38]. However, mild to moderate iodine deficiency still exists in a large fraction of pregnant women [21], and our results applying to pregnant women from this region may deviate from results obtained for female populations with other iodine and selenium status.…”
Section: Discussioncontrasting
confidence: 57%
“…The positive correlation between t-Pb and GPX1 can be ascribed to the antioxidant and detoxification function of this enzyme. Negative correlation between p-Se and T3 was somewhat unexpected as judged from the results of animal experiments, but associations can occur in humans [39][40][41].…”
Section: D1 (Pmol I/h/mg Protein)mentioning
confidence: 99%
“…There was no arbitrary criterion for excluding the subjects with Hashimoto disease from statistical analysis. The inclusion/exclusion criteria of healthy subjects were the same as in our previous reports (3,4). The local Ethical Committee approved the studies reported.…”
Section: Introductionmentioning
confidence: 99%
“…The patients' physical examination by an endocrinologist was the same as previously (3,4). To ensure pertinent time of sampling, the subjects were instructed about the importance of that issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation